Intrumentation for chemistry education using low cost materials (Research, Society and Development, 2019)
The chemistry teaching process is essential during children and teenagers learning process of the various concepts of science. However, sometimes, it is not successful because of the absence of practical experiments. For this reason, this paper aimed to build chemistry teaching materials using low cost products for high schools of João Monlevade city, state of Minas Gerais. These materials were produced aiming to create a new teaching concept through practical experiments easily executed and that could be presented in chemistry educational events in a funny and playful way. The purpose of these materials is to associate the theoretical knowledge present in class with the practice experience, checking if with the observation of an experiment it is possible to explain/understand the chemistry process involved in it. This project achieved its aim in a successful way for the teachers and the students. It confirmed that though a simple and didactic experimentation and the use of daily-life products can motivate scientific experiments.